Contagious Bovine Pleuropneumonia: A Passage to India - Robin A. J. Nicholas (Animals, 2023)
The World Organization for Animal Health (WOAH)-listed contagious bovine pleuropneumonia (CBPP) emerged first in Europe and then spread to Eastern Asia, including Japan and China, from the Northern Territories of Australia at the end of the 19th century. Its route to India, however, is less well known as there is little evidence for large importations of cattle from Australia. The lack of accurate diagnostic tests at this time meant veterinary authorities relied solely on clinical and pathological signs, many of which were non-specific. Consequently, any diagnoses of CBPP reported in the early 20th century must be viewed with caution. More convincing reports of CBPP confirmed by laboratory tests were made in the 1930s and 1940s in the Indian state of Assam. Eradication campaigns began in the 1940s with immunizations of live attenuated vaccines and then more comprehensively in the 1950s and 1960s, supplemented with serological screening and the establishment of quarantine centres at international borders. The last case of CBPP, reported to WOAH, was seen in 1990, but the launch of a new awareness campaign in Assam in 2002 and recent reports of the disease in Pakistan suggests the disease has persisted in the Indian subcontinent well into the 21st century.